First evidence for the presence of aquaporins in stallion sperm. (20th October 2017) - Bonilla‐Correal, S; Noto, F; Garcia‐Bonavila, E; Rodríguez‐Gil, JE; Yeste, M; Miro, J
Contents: Aquaporins (AQPs) are transmembrane proteins found in all cells and are responsible for the transport of water and small solutes. While these proteins have been found in the spermatozoa of humans, rodents, pigs and cattle, where not only do they play a role for the regulation of sperm volume but are also related with the sperm resilience to withstand freeze–thawing procedures, their presence in stallion sperm is yet to be reported. Therefore, the objectives of this work were as follows: (i) to determine whether AQP3, AQP7 and AQP11 are present in stallion sperm and (ii) to investigate whether the relative amounts of these three AQPs play any role in the cryopreservation success. With this purpose, a total of five ejaculates from healthy stallions were collected. Evaluation of sperm quality and immunoblotting against these three proteins were performed before and after cryopreservation. Immunoblots confirmed the presence of AQP3, AQP7 and AQP11 in all examined samples. Subsequently, ejaculates were classified as GFE (good) and PFE (poor freezability ejaculates), according to their sperm viability and motility at 0 and 2 hr post‐thaw. Relative AQP3 and AQP11 contents in stallion fresh semen were found to be significantly ( p  <   .05) higher in GFE than in PFE. In conclusion, the current study has confirmed, for the first time, the presence of AQP3, AQP7 and AQP11 in stallion sperm. In addition, despite preliminary, our results suggest that AQP3 and AQP11 are involved in the resilience of stallion sperm to withstand cryopreservation. Ongoing research is aimed at increasing the sample size and includes immunolocalization studies.